Progressive impairment of testicular endocrine function in ageing men: Testosterone and dihydrotestosterone decrease, and luteinizing hormone increases, in men transitioning from the 8th to 9th decades of life. (10th October 2017) - Yeap, Bu B.; Manning, Laurens; Chubb, S. A. Paul; Handelsman, David J.; Almeida, Osvaldo P.; Hankey, Graeme J.; Flicker, Leon
Summary: Context: Sex hormone trajectories in ageing men and their health implications remain unclear. We examined longitudinal trajectories and associations of testosterone (T), dihydrotestosterone (DHT), oestradiol (E2), luteinizing hormone (LH) and sex hormone‐binding globulin (SHBG) in oldest old men. Design: Prospective cohort study. Participants: We studied 1025 community‐dwelling men median age 75.1 years at baseline with 8.6 years of follow‐up. Measurements: Baseline and follow‐up T, DHT and E2 were assayed using mass spectrometry. Physical performance was assessed at follow‐up. Correlations and covariate‐adjusted P ‐values were determined. Results: Longitudinal change in T was −2.0%/year, DHT −7.2%/year, LH +7.5%/year, SHBG +5.6%/year while E2 remained stable. Annualized increases in LH correlated with decreases in T and DHT ( r = −.20, P < .0001 and r = −.12, P = .0035, respectively). Higher baseline T correlated with better physical performance at follow‐up (eg, Step test r = .07, P = .03), as did higher baseline DHT (eg, time to sit–stand [TSS] r = −.07, P = .01). Larger annualized increases in LH predicted poorer physical performance at follow‐up (eg, TSS r = .14, P = .001). Higher T at follow‐up was associated with better physical performance (eg, TSS r = −.07, P = .04), as were higher DHT and lower LH. At baseline, 24 men (2.4%) had abnormally high LH (>16 IU/L); at follow‐up, 175 (17.4%) had high LH of whom 70 had low T (<6.4 nmol/L). Conclusions: Annualized increases in LH are associated with declines in T and DHT, and predict poorer subsequent physical performance in oldest old men. Men transitioning from 8th to 9th decades exhibit biochemical evidence of progressively impaired testicular endocrine function, warranting further evaluation.